1996
DOI: 10.1007/bf01875582
|View full text |Cite
|
Sign up to set email alerts
|

Stress responses of Atlantic salmon (Salmo salar L.) elicited by water level reduction in rearing tanks

Abstract: The Atlantic salmon (Salmo salar) stress response was examined by measuring plasma cortisol, glucose and chloride in fish after water level reduction within rearing tanks. Maximum plasma cortisol levels (366±43 (SD) nM and 534±280 nM for Groups 1 and 2, respectively) were observed 20 min after application of the stressor. Cortisol levels were down to control levels 24 h later. The pattern for cortisol changes observed within these two groups were comparable. Plasma glucose and chloride concentrations did not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
21
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 27 publications
16
21
1
Order By: Relevance
“…The magnitude of the cortisol response following confinement was also higher in SW smolts. Cortisol concentrations measured in this study were similar to those previously recorded for Atlantic salmon in FW (Thorpe et al, 1987;Boesgaard et al, 1993;Olsen et al, 1995;Einarsdottir & Nilssen, 1996) and SW smolts (Waring et al, 1992;Sverdrup et al, 1994;Olsen et al, 1995;Einarsdottir & Nilssen, 1996). The increase in resting plasma cortisol levels of salmonids during smoltification, seaward migration and acclimation to SW, is well documented (Redding et al, 1984;Barton et al, 1985;Bjornsson et al, 1987;Thorpe et al, 1987;Barton & Iwama, 1991;Bisbal & Specker, 1991;Fuentes et al, 1996).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The magnitude of the cortisol response following confinement was also higher in SW smolts. Cortisol concentrations measured in this study were similar to those previously recorded for Atlantic salmon in FW (Thorpe et al, 1987;Boesgaard et al, 1993;Olsen et al, 1995;Einarsdottir & Nilssen, 1996) and SW smolts (Waring et al, 1992;Sverdrup et al, 1994;Olsen et al, 1995;Einarsdottir & Nilssen, 1996). The increase in resting plasma cortisol levels of salmonids during smoltification, seaward migration and acclimation to SW, is well documented (Redding et al, 1984;Barton et al, 1985;Bjornsson et al, 1987;Thorpe et al, 1987;Barton & Iwama, 1991;Bisbal & Specker, 1991;Fuentes et al, 1996).…”
Section: Discussionsupporting
confidence: 88%
“…Recovery of plasma cortisol levels in Atlantic salmon SW smolts was similar to previous studies in which a decline of plasma cortisol occurred from 2 to 8 h post-stress (Waring et al, 1992;Boesgaard et al, 1993;Einarsdottir & Nilssen, 1996). However, decline to pre-stress control levels can take 24-48 h in Atlantic salmon (Waring et al, 1992;Einarsdottir & Nilsen, 1996).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A similar finding was reported by Einarsdottir & Nilssen (1996), who demonstrated that Atlantic salmon Salmo salar L., subjected every third day to an acute stressor (water level reduction), showed a 42% reduced maximum level and a faster recovery after the fifth challenge compared with the maximum level and recovery time found after the first challenge. However, given the experimental set-up used in the present experiment, a role of other factors like exhaustion of the interrenal cells or an altered clearance rate or feed-back mechanism cannot be excluded.…”
Section: Age Effect and Habituationsupporting
confidence: 89%
“…In our experiment, circulating cortisol reached low levels within 24-48 h of surgery independent of nutritional status, and then declining further to the baseline resting plasma levels reported by Barton and Iwama (1991), Einarsdottir and Nilssen (1996), and Olsen et al (1995). A return of plasma cortisol levels close to pre-stress levels (C1 fish) only 24 h after surgery is much faster than previously reported (see above and Sect.…”
Section: Cortisolcontrasting
confidence: 43%